ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN BELANJA PADA BPKAD PROVINSI JAWA BARAT - Fitriani, Lusi; Mulyandani, Vina Citra (Jurnal Riset Akuntansi, 2025)
This study aims to analyze the factors influencing budget absorption at the Regional Financial and Asset Management Agency (BPKAD) of West Java Province, which include budget planning, budget implementation, human resource competence, and the procurement of goods and services. The research employs a quantitative approach with a population of 159 employees, and a sample of 46 financial management officials selected through purposive sampling. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression with the help of SPSS 26 software. The results show that budget planning and the procurement of goods and services have a significant partial effect on budget absorption. Meanwhile, budget implementation and human resource competence do not have a significant partial effect. Simultaneously, all four variables significantly influence budget absorption. Keywords: Budget Absorption, Budget Planning, Budget Implementation, Human Resource Competence, Procurement of Goods and Services.